Dual Effect of Manganese Oxide Micromotors: Catalytic Degradation and Adsorptive Bubble Separation of Organic Pollutants. Issue 4 (16th December 2015) - Wani, Owies M.; Safdar, Muhammad; Kinnunen, Niko; Jänis, Janne
Abstract: Manganese oxide (MnO2 ) based micromotors exhibiting a dual effect, that is, catalytic degradation and adsorptive bubble separation, were employed for water remediation. The dual effect of MnO2 microparticles led to a greater than 90 % of decolorization of non‐biodegradable organic dyes in just 1 h, without the need for external agitation or bubble generation. These findings suggest high potential of MnO2 micromotors for decontamination of organic pollutants from wastewaters or natural water reserves. Abstract : Manganese oxide (MnO2 ) based micromotors were employed for water remediation. The dual effect of MnO2 microparticles led to a greater than 90 % of decolorization of non‐biodegradable organic dyes in just 1 h, without the need for external agitation or bubble generation. These findings suggest high potential of MnO2 micromotors for decontamination of organic pollutants from wastewaters or natural water reserves.